Using Virtual Tours to Facilitate Sustainable Site Visits of Historic Sites - George, Benjamin H. (European Journal of Sustainable Development, 2018)
Many university-level design programs send their students on travel trips to notable examples of design across the globe. However, it is increasingly expensive for both students and programs to commit to extensive travel, and the accelerated growth of global tourism has led to increased pressure on many sensitive historical sites. However, the use of virtual tours may provide a learning experience for students that provides many of the learning affordances of an on-site visit; but does so in a more sustainable manner by reducing financial costs for institutions and lower visitor numbers for historical sites. This paper reports the findings of a program using 360-degree virtual tours in a landscape architecture history course to test students’ ability to spatially encode a site. The results found that students who visit a site using a virtual tour have significantly improved spatial encoding and improved performance on testing of factual knowledge related to the site, suggesting that students experienced many of the similar learning affordances of being on site. This would indicate that virtual tours can provide an opportunity for universities to provide students with a sustainable learning opportunity similar to what would be achieved through a physical visit to a site. Keywords: Landscape architecture history, constructivism, situated learning, visualization, virtual tour